Case Report: Bell’s palsy: a neurological manifestation of COVID-19 infection [version 2; peer review: 2 approved, 1 approved with reservations] - Amro Abdelrahman; Amira Bitar; Mohamed Elgassim; Isra Babiker; Fawaz Elgak (F1000Research)
Background Coronavirus (COVID-19) is the causative agent of the most recent pandemic that hit the globe and has been the cause of a vast range of symptoms, including neurological symptoms. Bell’s palsy is an acute peripheral facial paralysis commonly associated with viral infections. Case presentation This case report describes a patient with incidental COVID-19 infection that led to acute unilateral peripheral facial paralysis, Bell’s palsy. Our patient is a 35-year-old male with no known comorbidities who was presenting with upper respiratory tract infection symptoms and was found to be positive for COVID-19. Soon after the onset of symptoms, he also developed right-sided facial weakness in association with his symptoms. A thorough examination revealed a peripheral neurological lesion. The diagnosis of Bell’s palsy secondary to COVID-19 virus infection was through the exclusion of other possible causes. Conclusions This case report suggests a potential link between Bell’s palsy and COVID-19, highlighting the importance of a comprehensive understanding of the neurological manifestations of COVID-19. Further research is essential to determine the significance of neuropathies in COVID-19 and enhance treatment strategies.